A Problem-Solving and Student-Centred Approach to the Translation of Cultural References - González Davies, Maria; Scott-Tennent, Christopher (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractExploring possible answers to questions such as “Can we translate a cultural reference?” or even “What is a cultural reference?” is a highly relevant issue for translation students. These are matters that have been addressed by academics and full time translators alike, and no final or definite solutions have been found to the problems generated by the uncertainties, just as there are no final or definitive definitions of the concept of culture itself.In an attempt to help and guide our students to improve this specific aspect of translation competence, a syllabus was designed within a pedagogical setting based on humanistic and socioconstructivist principles as well as on task and project-based learning, and an experimental study was carried out within that pedagogical setting to explore specific effects of such training. In this article, we will deal mainly with the experimental training itself, whereas the study will be reported on in a forthcoming publication.